BUNDLING NETWORKS FOR INTERMODAL FREIGHT FLOWS TO THE EUROPEAN HINTERLAND (Perner's Contacts, 2012)
This paper compares bundling concepts for various situations, and suggests the development of inland services contrary to the simultaneous situations. All matters are carried out for configuration and bundling in the Hamburg-Rotterdam range (H-R range), with focus on the bundling in rail networks, and bundling in barging networks of container flows to the central Europe. The challenge is to identify promising directions of intermodal network development.
Keywords: intermodal transport, container, bundling, terminal